PC / ABS composite material and preparation method thereof
By preparing a modified anti-UV agent in a PC/ABS composite, grafted by urottropine, para-aminophenol and styrene, combining 6-(1,3-dihydro-2H-benzo[d][ 1,2,3] Triazole-2-yl)-7-hydroxynaphthalene-2-sulfonate sodium solves the problem of insufficient anti-ultraviolet aging performance of existing materials and significantly improves the light resistance stability of the materials.
Patent Information
- Application Number
- CN202411608771.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing PC/ABS composites have poor UV aging resistance and are difficult to meet the higher photo-resistant aging needs.
The tan polymer was prepared by reaction of ulotropine with p-aminophenol and grafted with glycidyl methacrylate and styrene, followed by 6-(1,3-dihydro-2H-benzo[d] [1,2,3] Triazole-2-yl)-7-hydroxynaphthalene-2-sulfonate reaction prepares a modified anti-UV agent to improve the material's UV resistance.
Modified anti-UV ray agent significantly improves the anti-UV aging performance in PC/ABS composite materials, solves the problem of poor mixing uniformity of traditional benzotriazole UV absorbers, prevents UV migration and volatility, and enhances the light resistance and stability of the material. sex.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a PC / ABS composite material and a preparation method thereof. Background Art
[0002] PC / ABS composite is an important engineering plastic alloy that combines the excellent properties of polycarbonate (PC) and acrylonitrile-butadiene-styrene (ABS). It offers excellent molding flow properties, low-temperature impact resistance, and a high heat distortion temperature. Therefore, it is widely used in a wide range of fields, including household appliances, office equipment, communications equipment, photographic equipment, medical equipment, construction and lighting, as well as aerospace, electronic computers, and optical fiber. In recent years, with the rapid development of industries such as automobiles and home appliances, PC / ABS has placed higher performance requirements on these materials, requiring not only superior bending and tensile properties but also light aging resistance.
[0003] Chinese invention patent publication number CN117820839A discloses a high-toughness PC / ABS composite material, which is composed of the following raw materials in parts by weight: PC: 60-70 parts, ABS: 30-40 parts, compatibilizer: 3-5 parts, toughening agent: 3-6 parts, flame retardant: 2-4 parts, and antioxidant: 0.5-1 part; the high-toughness PC / ABS composite material prepared in its optimal embodiment has a tensile strength of 79.6 MPa and a flexural strength of 89.2 MPa, but its resistance to ultraviolet aging is poor. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide a PC / ABS composite material and a preparation method thereof.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions: A PC / ABS composite material comprises the following raw materials in parts by weight: PC: 60-70 parts, ABS: 30-40 parts, toughening agent: 3-6 parts, modified anti-ultraviolet agent 2-3 parts, flame retardant: 2-4 parts, antioxidant: 0.5-1 part, the modified anti-ultraviolet agent is prepared by the following method: S1: Hexamethylenetetramine reacts with p-aminophenol in the presence of glacial acetic acid as a catalyst to produce a brown polymer. The reaction equation is as follows:
[0006] S2: Under nitrogen protection, the brown polymer, glycidyl methacrylate, and styrene react in the presence of catalyst C-94 and 1-butyl-3-methylimidazolium methanesulfonate ionic liquid to obtain a grafted polymer. The reaction equation is as follows:
[0007] Among them, m=o+p+q, m, o, p, q are natural numbers.
[0008] S3: Sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate, grafted polymer, DMF, and NaOH were sequentially added to a stirred reactor and refluxed for 8-14 hours. During the reaction, acetone was added to reduce the viscosity, and then deionized water was added for high-speed dispersion for 1-1.5 hours. Finally, the modified UV inhibitor was obtained by rotary evaporation at 40-50°C. The reaction equation is shown as follows:
[0009] Where o=s+t, s and t are natural numbers.
[0010] The feed ratio of DMF, sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate, grafted polymer and NaOH is 30:(6-8):(3-5):(0.1-0.12).
[0011] The toughening agent is methyl methacrylate / butadiene / styrene copolymer.
[0012] The flame retardant is one of triphenyl phosphate, tricresyl phosphate and cresyl diphenyl phosphate.
[0013] The antioxidant is one of antioxidant 1010, antioxidant 1076, and antioxidant 168.
[0014] A method for preparing a PC / ABS composite material comprises the following steps: S1: Dry PC and ABS in a blast drying oven at 90-100°C for 5-10 hours respectively and set aside; S2: Weigh the raw materials according to the ratio and mix them evenly; S3: The mixed raw materials are placed in the main feeding bin of the twin-screw extruder, and added into the main barrel of the extruder through the feeding screw for melt extrusion, wherein: the screw diameter of the twin-screw extruder is 35 mm, the aspect ratio L / D=36, the feeding screw speed is 25 r / min, and the main barrel is divided into nine sections for temperature control; the temperatures from the feeding port to the die outlet are 200°C, 230°C, 255°C, 255°C, 255°C, 255°C, 255°C, 240°C in sequence, and the twin-screw speed is 300 rpm; finally, the extruded material strips are cooled in a water tank and then pelletized to obtain a high-toughness PC / ABS composite material.
[0015] Due to the adoption of the above technical solution, the beneficial effects of the present invention include: (1) The present invention prepares a brown polymer by using urotropine and p-aminophenol, then grafts the brown polymer with glycidyl methacrylate and styrene to prepare a new graft polymer, and finally reacts the graft polymer with sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate to prepare a modified UV inhibitor.
[0016] (2) The modified UV-resistant agent prepared by the present invention contains styrene grafted groups and epoxy groups provided by glycidyl methacrylate, so that the prepared modified UV-resistant agent has good compatibility with PC and ABS, solving the problem of poor mixing uniformity of traditional benzotriazole UV absorbers; by combining with the grafted polymer, a high molecular polymer with benzotriazole is obtained, which has the performance of absorbing ultraviolet rays and prevents its migration and volatilization problems, thereby improving the anti-ultraviolet aging performance of PC / ABS composite materials. DETAILED DESCRIPTION
[0017] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to these embodiments.
[0018] Example 1
[0019] Preparation of grafted polymers: S1: 1 kg of deionized water, 0.25 kg of hexamethylenetetramine, 0.1 kg of p-aminophenol, and 0.08 kg of glacial acetic acid were added to a reactor in sequence, stirred and dissolved, and heated to 75°C for 3 h. The mixture was cooled to room temperature and separated into layers. The aqueous layer was separated and washed three times with deionized water (200 g of deionized water each time) to obtain a brown polymer. S2: 3kg DMF, 0.8kg brown polymer, 0.5kg glycidyl methacrylate, 0.2kg styrene, 0.01kg catalyst C-94, and 0.008kg 1-butyl-3-methylimidazolium methane sulfonate ionic liquid were added to the reactor in sequence, protected by nitrogen, heated to 100°C, reacted for 5h, cooled to room temperature, added with 4kg deionized water and stirred evenly, centrifuged, washed with 0.4kg anhydrous ethanol and then with 0.4kg deionized water, and dried in vacuo at 80°C for 10h to obtain a grafted polymer.
[0020] Example 2
[0021] Preparation of sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate: Add 22.2g of o-nitroaniline, 40ml of hydrochloric acid (36.5wt%), and 200ml of water to a 1000ml flask. Stir at 30°C for 30 minutes, then cool to 0-5°C. Slowly add 10ml of a 4wt% sodium nitrite aqueous solution dropwise. Allow to react for another 30 minutes, then add 12ml of urea (20wt%) to produce the diazonium salt. Weigh 39.4g of 2-naphthol-6-sulfonic acid sodium hydrate to a 2500ml three-necked flask, then add 10.5ml of saturated sodium carbonate solution to adjust the pH to 7-8. Place in an ice-water bath, and add 15g of the aforementioned diazonium salt with stirring. Maintain the temperature at 0-5°C and react for 2 hours to produce the 2-naphthol-7-sulfonic acid azo-o-nitrobenzene intermediate. 20 g of the above intermediate, 200 ml of ethanol, and 4 g of NaOH were added to a three-necked flask, heated to reflux, and then 1.74 g of sodium dithionite was added. The reaction was continued for 1 hour, cooled to room temperature, acidified with 50 ml of hydrochloric acid solution (36.5 wt%), and filtered. The filter cake was washed with 400 g of anhydrous ethanol, dried at 50° C., and then ground into powder in a mortar to obtain sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate.
[0022] Example 3
[0023] Preparation of modified UV inhibitor: 300 g of DMF, 60 g of sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate (prepared in Example 2), 30 g of the grafted polymer (prepared in Example 1), and 1 g of NaOH were sequentially added into a stirred reactor and refluxed for 8 h. During the reaction, 23 g of acetone was added, followed by 120 ml of deionized water and high-speed dispersion for 1 h. Finally, the mixture was rotary evaporated at 40° C. to obtain a modified UV inhibitor.
[0024] Example 4
[0025] Preparation of modified UV inhibitor: 300 g of DMF, 70 g of sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate (prepared in Example 2), 40 g of the grafted polymer (prepared in Example 1), and 1.1 g of NaOH were sequentially added into a stirred reactor and refluxed for 11 h. During the reaction, 23 g of acetone was added, followed by 120 ml of deionized water and high-speed dispersion for 1.5 h. Finally, the mixture was rotary evaporated at 45° C. to obtain a modified UV inhibitor.
[0026] Example 5
[0027] Preparation of modified UV inhibitor: 300 g of DMF, 80 g of sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate (prepared in Example 2), 50 g of the grafted polymer (prepared in Example 1), and 1.2 g of NaOH were sequentially added into a stirred reactor and refluxed for 14 h. During the reaction, 23 g of acetone was added, followed by 150 ml of deionized water and high-speed dispersion for 1 h. Finally, the mixture was rotary evaporated at 50° C. to obtain a modified UV inhibitor.
[0028] Example 6
[0029] A PC / ABS composite material comprising the following raw materials: PC: 6 kg, ABS: 3 kg, modified UV inhibitor (prepared in Example 3): 0.2 kg, toughening agent (methyl methacrylate / butadiene / styrene copolymer): 0.3 kg, flame retardant (triphenyl phosphate): 0.2 kg, antioxidant (antioxidant 1010): 0.05 kg.
[0030] The above components of corresponding weights were weighed, stirred evenly, and then added into a twin-screw extruder for melt extrusion and granulation.
[0031] Example 7
[0032] A PC / ABS composite material comprising the following raw materials: PC: 6.5 kg, ABS: 3.5 kg, modified UV inhibitor (prepared in Example 4): 0.25 kg, toughening agent (methyl methacrylate / butadiene / styrene copolymer): 0.45 kg, flame retardant (tricresyl phosphate): 0.3 kg, antioxidant (antioxidant 1076): 0.075 kg.
[0033] The above components of corresponding weights were weighed, stirred evenly, and then added into a twin-screw extruder for melt extrusion and granulation.
[0034] Example 8
[0035] A PC / ABS composite material comprising the following raw materials: PC: 7 kg, ABS: 4 kg, modified UV inhibitor (prepared in Example 5): 0.3 kg, toughening agent (methyl methacrylate / butadiene / styrene copolymer): 0.6 kg, flame retardant (cresyl diphenyl phosphate): 0.4 kg, antioxidant (antioxidant 168): 0.1 kg.
[0036] The above components of corresponding weights were weighed, stirred evenly, and then added into a twin-screw extruder for melt extrusion and granulation.
[0037] Comparative Example 1 The raw material composition and the number of parts of the PC / ABS composite material are basically the same as those in Example 7, except that no modified anti-ultraviolet agent is added to the composition.
[0038] Comparative Example 2 The composition and number of raw materials of the PC / ABS composite material are basically the same as those in Example 7, except that 0.25 kg of the modified anti-ultraviolet agent is replaced by 0.25 kg of sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate.
[0039] Comparative Example 3 The composition and number of raw materials of the PC / ABS composite material are basically the same as those in Example 7, except that 0.25 kg of the modified anti-ultraviolet agent is replaced by 0.16 kg of sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate and 0.9 kg of the grafted polymer.
[0040] Comparative Example 4 The raw material composition and the number of parts of the PC / ABS composite material are basically the same as those in Example 7, except that the modified anti-ultraviolet agent is replaced with 0.25 kg UV-326 (CAS No.: 3896-11-5).
[0041] Comparative Example 5 The raw material composition and number of parts of the PC / ABS composite material are basically the same as those in Example 7, except that the modified anti-ultraviolet agent is replaced by the modified antioxidant prepared in Example 3 of the Chinese invention patent publication number CN118440458A.
[0042] Comparative Example 6 The PC / ABS composite material is prepared by using the raw material composition of Example 6 of the Chinese invention patent with publication number CN117820839A and the production process of the present application.
[0043] The polycarbonate PC used in the examples and comparative examples of the present application is Lotte PC-1100, the ABS is Shanghai Gaoqiao ABS-3513, and the methyl methacrylate / butadiene / styrene copolymer is LG Chemical MBS EM500.
[0044] The preparation process of the PC / ABS composite materials involved in Examples 6-8 and Comparative Examples 1-6 of the present application is as follows: S1: Dry PC and ABS in a blast drying oven at 95°C for 10 hours respectively and set aside; S2: Weigh the raw materials according to the ratio and mix them evenly; S3: The mixed raw materials are placed in the main feeding bin of the twin-screw extruder, and are added into the main barrel of the extruder through the feeding screw for melt extrusion, wherein: the screw diameter of the twin-screw extruder is 35 mm, the aspect ratio L / D=36, the feeding screw speed is 25 r / min, and the main barrel is divided into nine sections for temperature control; the temperatures from the feeding port to the die outlet are 200°C, 230°C, 255°C, 255°C, 255°C, 255°C, 255°C, 240°C in sequence, and the twin-screw speed is 300 rpm; finally, the extruded material strips are cooled in a water tank and then pelletized to obtain PC / ABS composite materials.
[0045] The PC / ABS composite materials prepared in Examples 6-8 of the present application and Comparative Examples 1-6 were tested for tensile strength, flexural strength, notched impact strength and UV resistance. The test results are shown in Table 1.
[0046] The tensile strength test method is in accordance with ASTM D-638 standard. The specimen size is 120 mm in length, 10 mm in width, and 4 mm in thickness. The tensile rate in the experiment is set at 50 mm / min.
[0047] The flexural strength test method was in accordance with ASTM D-790, with the specimen dimensions being 80 mm in length, 10 mm in width, and 4 mm in thickness, the travel rate being set at 2 mm / min, and the span being 52 cm.
[0048] The notched impact strength test method is in accordance with ASTM D-256 standard, with the specimen size being 62.5 mm in length, 12.7 mm in width, 4 mm in thickness, 2.54 mm in notch depth, and an impact load of 5.5 J.
[0049] Anti-ultraviolet aging performance test: The PC / ABS engineering plastics prepared in Examples 6-8 of the present application and Comparative Examples 1-6 were made into test specimens with a length of 120 mm, a width of 10 mm, and a thickness of 4 mm. The specimens were placed in an aging box with a 1000W high-pressure mercury lamp and 80°C for continuous irradiation for 1000 hours; after aging, the tensile strength was tested according to the ASTM D-638 standard.
[0050] Table 1
[0051] It can be seen from Table 1 that the PC / ABS composite materials prepared in Examples 6 to 8 of the present application have excellent tensile strength, flexural strength, notched impact strength and UV resistance.
[0052] Comparative Example 1 is a comparative example of a PC / ABS composite material prepared without adding a modified anti-ultraviolet agent. From the data in Table 1, it can be seen that its tensile strength after aging is 43.8 MPa.
[0053] The modified anti-ultraviolet agent added in Comparative Example 2 is sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate. As can be seen from Table 1, its strength after aging is 54.7 MPa.
[0054] The modified UV inhibitor added in Comparative Example 3 is sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate and a grafted polymer. As can be seen from Table 1, the tensile strength after aging is 52.4 MPa.
[0055] Comparative Example 4 is a comparative example in which a modified UV-resistant agent UV-326 is added, and its tensile strength after aging is only 55.9 MPa.
[0056] Comparative Example 5 is a modified antioxidant prepared using Example 3 of the Chinese invention patent publication number CN118440458A, and its tensile strength after aging is 58.2 MPa.
[0057] Comparative Example 6 uses the raw material composition of Example 6 of the Chinese invention patent publication number CN117820839A, and its tensile strength after aging is 46.7 MPa.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in this field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the scope of protection of the technical solution of the present invention.
Claims
1. A PC / ABS composite material, characterized in that: The invention comprises the following raw materials in parts by weight: PC: 60-70 parts, ABS: 30-40 parts, toughening agent: 3-6 parts, modified anti-ultraviolet agent 2-3 parts, flame retardant: 2-4 parts, antioxidant: 0.5-1 parts, the modified anti-ultraviolet agent is prepared by the following method: S1: Hexamethylenetetramine reacts with p-aminophenol in the presence of glacial acetic acid as a catalyst to obtain a brown polymer; S2: under nitrogen protection, brown polymer, glycidyl methacrylate and styrene react in the presence of catalyst C-94 and 1-butyl-3-methylimidazolium methanesulfonate ionic liquid to obtain a grafted polymer; S3: Sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate, grafted polymer, DMF and NaOH are added to a stirred reactor in sequence and refluxed for 8-14 hours. During the reaction, acetone is added to reduce the viscosity, and then deionized water is added for high-speed dispersion, followed by rotary evaporation to obtain a modified UV inhibitor.
2. A PC / ABS composite material according to claim 1, characterized in that: In the step S3, the feed ratio of DMF, sodium 6-(1,3-dihydro-2H-benzo[d][1,2,3]triazol-2-yl)-7-hydroxynaphthalene-2-sulfonate, grafted polymer and NaOH is 30:(6-8):(3-5):(0.1-0.12).
3. A PC / ABS composite material according to claim 1, characterized in that: The toughening agent is methyl methacrylate / butadiene / styrene copolymer.
4. A PC / ABS composite material according to claim 1, characterized in that: The flame retardant is one of triphenyl phosphate, tricresyl phosphate and cresyl diphenyl phosphate.
5. The PC / ABS composite material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010, antioxidant 1076 and antioxidant 168.
6. A method for preparing the PC / ABS composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Dry PC and ABS in a blast drying oven at 90-100°C for 5-10h respectively for later use; S2: weigh the raw materials according to the ratio and mix them evenly; S3: placing the mixed raw materials in the main feeding bin of a twin-screw extruder, adding them into the main barrel of the extruder through the feeding screw for melt extrusion, wherein: the screw diameter of the twin-screw extruder is 35 mm, the aspect ratio L / D=36, the feeding screw speed is 25 r / min, and the main barrel is divided into nine sections for temperature control; the temperatures from the feeding port to the die outlet are 200°C, 230°C, 255°C, 255°C, 255°C, 255°C, 255°C, 240°C, respectively, and the twin screw speed is 300 rpm; finally, the extruded material strips are cooled in a water trough and pelletized to obtain a PC / ABS composite material.
Citation Information
Patent Citations
High-toughness PC / ABS composite material and preparation method thereof
CN117820839A
Anti-aging ABS engineering plastic and preparation method thereof
CN118440458A
